PHYSICAL LITERACY PUBLICATION TRENDS IN INDONESIA USING BIBLIOMETRIC ANALYSIS - Hayudi, H; Suherman, Adang; Sutresna, Nina; Yudiana, Yunyun (Universitas Pendidikan Indonesia, 2024)
This research aims to link mapping analysis with VOSviewer software in bibliometric engineering research on physical literacy in Indonesia. The results of this mapping can be used as a reference and help researchers to decide on future research themes, especially those related to physical literacy. The Publis or Perish application is used to search and collect databases based on Google Scholar. Titles, keywords, and abstracts are part of the bibliographic mapping data used in this research. The search results collected 989 articles published over 11 years (2013-2023). Based on the number of publications on physical literacy in Indonesia from 2013-2023 it is unstable. 2021 will be the peak publication of 240 articles. Research on the topic of physical literacy in Indonesia is still very lacking and is wide open for research, mainly including physical literacy in educational unit curricula, physical literacy is linked to knowledge, physical literacy is linked to elementary schools, physical literacy is related to national development policies.